PENGARUH PERTUMBUHAN PENJUALAN, KEBIJAKAN UTANG DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK - Azzahra, Khoirunnisa (Politeknik Raflesia Press, 2023)
In optimizing tax collection there are many obstacles, one of which is the form of taxpayer non-compliance in paying taxes. The phenomenon of tax evasion and other tax aggressiveness in Indonesia is still rife in various business sectors. The aim of this study was to determine the effect of sales growth, debt policy, and liquidity on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2016 until 2021. This research uses a type of quantitative research with an associative method with a population of 66 companies and a sample of 5 companies. Determination of the sample using the passive sampling method, the type of data used is secondary data with data analysis using the panel data regression model with the help of the eviews 9 application. Based on the test results it was found that, sales growth no effect on tax aggressiveness, debt policypositive effect on tax aggressiveness, liquidity has no effect against tax aggressiveness.